1989
DOI: 10.1111/j.1349-7006.1989.tb01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HTLV‐I Genome in Seronegative Infants Born to HTLV‐I Seropositive Mothers by Polymerase Chain Reaction

Abstract: We applied the polymerase chain reaction (PCR) method to detect gag, env and pX sequences of human T cell leukemia virus type I (HTLV‐I) provirus in peripheral blood lymphocytes of seronega‐tive infants born to HTLV‐I seropositive mothers. Out of 22, five subjects were found to contain the HTLV‐I provirus genome. Two of the five cases were judged to be negative for not only anti‐HTLV‐I antibodies but also the viral antigens on cultivated lymphocytes by the conventional antibody/antigen detection methods. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In general, HTLV-1-infected individuals have antibodies to structural proteins of the virus. However, it has been reported that some virus carriers and individuals with HTLV-1-associated diseases do not have detectable antibodies to HTLV-1 structural proteins [10][11][12][13][14] . Most virus carriers remain asymptomatic during their life, and the cofactors required for disease progression are largely unknown.…”
mentioning
confidence: 99%
“…In general, HTLV-1-infected individuals have antibodies to structural proteins of the virus. However, it has been reported that some virus carriers and individuals with HTLV-1-associated diseases do not have detectable antibodies to HTLV-1 structural proteins [10][11][12][13][14] . Most virus carriers remain asymptomatic during their life, and the cofactors required for disease progression are largely unknown.…”
mentioning
confidence: 99%
“…Therefore, based on these results, it is concluded that the overall incidence of vertical transmission is relatively low (33.3%, four infants/twelve HCV antibody seropositive mothers; 57%, four infants/seven HCV-RNA seropositive mothers). This incidence is the same as that of HTLV-1(human T-cell leukemia virus type-1; almost 40% in cases of breast feeding (Saito et al 1990)) but less than that of HBV (hepatitis B virus; 70% in HBs and HBe antigens positive women (Biswac et al 1989)). …”
Section: Resultsmentioning
confidence: 63%
“…While in the majority of cases HTLV-I/II sequences are not detected by PCR, there are some cases in which it is possible to amplify by PCR sequences of different HTLV-I/II genes (Saito et al 1989, Delaporte et al 1991, Miyata et al 1995, since some of them become seropositive over time. The data reported suggests the existence of HTLV-I/II infected subjects who are serologically negative.…”
Section: Discussionmentioning
confidence: 99%